2017
DOI: 10.1186/s13643-016-0385-3
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic processing post traumatic brain injury - a systematic review

Abstract: BackgroundTraumatic brain injury (TBI) survivors often report difficulties with understanding and producing paralinguistic cues, as well as understanding and producing basic communication tasks. However, a large range of communicative deficits in this population cannot be adequately explained by linguistic impairment. The review examines prosodic processing performance post-TBI, its relationship with injury severity, brain injury localization, recovery and co-occurring psychiatric or mental health issues post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 60 publications
2
66
2
Order By: Relevance
“…Increased physical injuries following a TBI may occur because following a TBI an individual's ability to safely navigate their environment is significantly affected. [44,45] Future research should consider whether the adverse events associated with TBIs (e.g., substance use) are the main cause in the TBI-related increased risk of physical injuries, or whether the physical impairments brought about by a TBIs (e.g., loss of balance, and vision and auditory acute or chronic impairments) lead to higher risk of physical injuries following TBIs. [11,12,15,[18][19][20][21][22]45] Sports-related TBIs accounted for almost half of the TBIs reported in this study.…”
Section: Plos Onementioning
confidence: 99%
“…Increased physical injuries following a TBI may occur because following a TBI an individual's ability to safely navigate their environment is significantly affected. [44,45] Future research should consider whether the adverse events associated with TBIs (e.g., substance use) are the main cause in the TBI-related increased risk of physical injuries, or whether the physical impairments brought about by a TBIs (e.g., loss of balance, and vision and auditory acute or chronic impairments) lead to higher risk of physical injuries following TBIs. [11,12,15,[18][19][20][21][22]45] Sports-related TBIs accounted for almost half of the TBIs reported in this study.…”
Section: Plos Onementioning
confidence: 99%
“…Recent and prior meta-analytic reviews [ 9 , 12 , 13 ] have found that numerous well-controlled studies have strengthened the claim that physical exercise can positively impact cognitive functioning in later life. Reviews continue to call for more well-controlled clinical trials to incorporate innovations that will reach and engage pre-clinical cases such as MCI where cognitive decline might go undetected yet harbor underlying neuropathology that could potentially be ameliorated with intervention [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most maternal and neonatal deaths cluster around the day of birth. 1 It is difficult to predict which women will suffer complications 2 as they often occur rapidly without warning. 3 To save maternal and perinatal lives, skilled attendance at birth and access to a facility that provides Comprehensive Emergency Obstetric and Newborn Care are critical requirements for all labouring women 4 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 7–9 Poorer families are less likely to have facility-based deliveries because of problems funding transport, user fees and hidden costs of treatments. 2 5–7 Antenatal care (ANC) is associated with increased uptake of facility-based delivery, 5 7 as is urban residence 5 10–12 and increased time in education for the woman. 5 7 10 The impact of a woman’s ‘autonomy’ on facility-based delivery uptake is inconsistent in the literature.…”
Section: Introductionmentioning
confidence: 99%